2006
DOI: 10.1038/sj.ijo.0803198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weight reduction by sibutramine on female sexual function

Abstract: Background: It is well known that selective serotonin reuptake inhibitors (SSRIs) can cause sexual dysfunction, so it is possible that sibutramine, a serotonin and norepinephrine reuptake inhibitor, could induce sexual dysfunction. Design and subjects: The effect of sibutramine on sexual function was evaluated in 46 overweight and obese (body mass index (BMI) X23 kg/m 2 ) but otherwise healthy married women (28-44 years). Participants were randomly assigned at baseline to either the sibutramine or control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…Moreover, Larsen (2005) in a review of cross-sectional and prospective studies found a correlation between obesity and erectile dysfunction in men (18). Consistent with these findings, most weight-loss interventions have been associated with improved sexual function in both men and women (33)(34)(35). The results of a review conducted by Kolotkin et al also showed a higher incidence of sexual dysfunction in obese men and women compared to normal individuals.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, Larsen (2005) in a review of cross-sectional and prospective studies found a correlation between obesity and erectile dysfunction in men (18). Consistent with these findings, most weight-loss interventions have been associated with improved sexual function in both men and women (33)(34)(35). The results of a review conducted by Kolotkin et al also showed a higher incidence of sexual dysfunction in obese men and women compared to normal individuals.…”
Section: Discussionsupporting
confidence: 67%
“…However, it seems that weight loss helps to improve sexual performance in overweight women. Improved sexual function after weight reduction in obese young women is probably due to change in sex hormones, estrogen and androgens and improvement of body image (36). …”
Section: Discussionmentioning
confidence: 99%
“…Kolotkin et al [28] found that sexual quality of life improved with weight loss in women undergoing non-surgical treatment. In another study [29], weight losses achieved through an 8-week combination of sibutramine and behavioral intervention yielded improvements in FSFI total score and domain scores relating to arousal and lubrication. More recently, Kolotkin and colleagues [30] found improvements in sexual quality of life in female gastric bypass surgery patients at 2 years postoperatively.…”
Section: Discussionmentioning
confidence: 99%